Effect of prosthetic restoration on implant survival and success - Rammelsberg, Peter; Lorenzo Bermejo, Justo; Kappel, Stefanie (Clinical oral implants research, 2017)
The objective of this work was to evaluate the effect of prosthetic restoration on the survival of implants and on the incidence of implant-related complications. Material and methods From a prospectively documented clinical study, 1569 implants placed in 630 patients (mean age 59.56 years) were evaluated. Selection criteria were a conventional loading protocol, prosthetic restoration with at least one follow-up, and a minimum observation period of 9 months. Implants that failed before prosthetic restoration were excluded. The sample included 1345 tissue-level implants and 104 bone-level implants (Straumann), and 120 Replace implants (Nobel Biocare). The observation period ranged between 9 months and 11 years after prosthetic restoration (mean 4.0 years; SD 2.5). The implants were restored with single crowns (n = 557), fixed dental prostheses (n = 594), or removable dental prostheses (RDP) (n = 418). In the RDP group, 356 implants were restored with telescoping crowns, 22 with bar units 24 with bar joints, and 16 with locator attachments. The incidence of implant-related complications and failures was analyzed by use of Kaplan-Meier survival curves. Cox regression analysis was used to identify possible risk factors. Results Twenty-seven failures (1.8%; loosened or removed implants) were observed after prosthetic restoration; the incidence of failure was 3% for implants placed in males and 1% for implants placed in females. Other factors had no effect on the incidence of failure. Peri-implantitis (n = 29) and marginal bone loss >2 mm without acute inflammation (n = 6) also resulted in a 4% incidence of severe implant-related complications (62 of 1569; success 96%). Cox regression analysis revealed combined tooth-implant-supported restorations as a significant risk-reducing factor for severe implant-related complications (hazard ratio, HR = 0.34; P = 0.04). There was, furthermore, a tendency toward a greater incidence of complications for implants restored with RDPs than for single crowns (P = 0.08). Other factors, for example location (anterior/posterior, maxilla/mandible), age, sex, or implant placement combined with bone augmentation, had no significant effect on the incidence of implant-related complications (P values ranging between 0.16 and 0.94). Conclusions The type of support has a small but significant effect on implant prognosis. For detailed analysis of the effects of loading by different types of prosthetic restoration, larger sample sizes are required.